1988
DOI: 10.1002/job.4030090403
|View full text |Cite
|
Sign up to set email alerts
|

Multiple roles and organizational commitment

Abstract: Using role theory as a conceptual framework, the influence of extra‐organizational ties on the employee's level of organizational commitment is explored in the present study. Two competing models of the relationship between work and outside work ties are proposed: an expansion model which holds that individuals view the available supply of energy and effort as abundant and expandable, and a scarcity model which posits that strong commitment to one role may preclude attachment to other roles. The findings revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
1
4

Year Published

1993
1993
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 25 publications
2
24
1
4
Order By: Relevance
“…Kirchmeyer's findings, together with the findings of this research, support the spillover hypothesis, according to which individuals tend to cope with increasing organisational and extraorganisational role demands by responding positively to those demands (Randall, 1988). Adding new roles liberates a source of energy for the individual, and rather than having to pay for extensive social involvements, individuals may come away from new involvements more enriched and vitalised.…”
Section: Involvement In the Jobsupporting
confidence: 77%
See 1 more Smart Citation
“…Kirchmeyer's findings, together with the findings of this research, support the spillover hypothesis, according to which individuals tend to cope with increasing organisational and extraorganisational role demands by responding positively to those demands (Randall, 1988). Adding new roles liberates a source of energy for the individual, and rather than having to pay for extensive social involvements, individuals may come away from new involvements more enriched and vitalised.…”
Section: Involvement In the Jobsupporting
confidence: 77%
“…It posits a transference of beliefs, attitudes, and values learned in one setting to another. The degree of involvement at work will be directly related to the degree of involvement in social roles outside the workplace (Champoux, 1981;Randall, 1988). In addition, it is suggested that influences also flow from family and community to work (Crouter, 1984;Price, 1985).…”
Section: Conceptual Framework and Research Hypothesesmentioning
confidence: 97%
“…One widely accepted perspective, based on the concept of compatibility, contends that multiple commitments can coexist as long as they are aligned in terms of demands and content (Randall, 1988;Vandenberghe, 2009). When such alignment is missing, conflict is likely to arise (Johnson et al, 2010;Morin et al, 2011: Vandenberg & Scarpello, 1994.…”
Section: Research Path 5 Research On Workplace Commitment Inmentioning
confidence: 99%
“…That is, when we examine the association between work attitudes and overall life attitudes we are looking for spillover or correlation between two sets of attitudes. This does not test the spillover typical American workers may experience between the activities in their work situation and outside of work (Goode, 1960;Piotrkowski, 1979;Randall, 1988). For example, if one experiences role overload because of too many hours spent juggling work roles and roles outside work (Greenhaus and Beutell, 1985), this may not translate into changed attitudes regarding either domain.…”
Section: Study 2 Resultsmentioning
confidence: 94%